2019
DOI: 10.1108/jaee-10-2017-0096
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalisation of the Cash Basis International Public Sector Accounting Standard in the Central Government of Bangladesh

Abstract: Purpose -This paper examines public sector accounting reforms, mainly the adoption and implementation of the Cash Basis International Public Sector Accounting Standard (IPSAS) in the central government of Bangladesh.Design/Methodology/Approach -Drawing on the ideas of new institutionalism, the paper investigates the factors which have forced the country to accept the Cash Basis IPSAS but have delayed its implementation in practice.Findings -Different approaches towards the Cash Basis IPSAS are now distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 67 publications
(152 reference statements)
2
37
0
1
Order By: Relevance
“…This practice diversity challenges the global debate of public sector accounting harmonisation articulated by international organisations and standard setters (Argento et al, 2018). Next, extending the findings of prior work in emerging economies (Busca et al, 2016;Goddard et al, 2016;Adhikari et al, 2013 andRajib et al, 2019), we have illustrated why the diffusion of public sector accounting reforms and their adoption by emerging economies, as championed by international organisations, has remained ineffective in practice. As such reforms have not only experienced delay and resistance at the implementation stage, as they have been diffused and adopted de-emphasising the specific contextual elements, in many cases they have resulted in internal conflicts and unintended consequences, including the fabrication of results, without any evidence of yielding better results for public sector governance and accountability.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…This practice diversity challenges the global debate of public sector accounting harmonisation articulated by international organisations and standard setters (Argento et al, 2018). Next, extending the findings of prior work in emerging economies (Busca et al, 2016;Goddard et al, 2016;Adhikari et al, 2013 andRajib et al, 2019), we have illustrated why the diffusion of public sector accounting reforms and their adoption by emerging economies, as championed by international organisations, has remained ineffective in practice. As such reforms have not only experienced delay and resistance at the implementation stage, as they have been diffused and adopted de-emphasising the specific contextual elements, in many cases they have resulted in internal conflicts and unintended consequences, including the fabrication of results, without any evidence of yielding better results for public sector governance and accountability.…”
Section: Discussionsupporting
confidence: 54%
“…Russia and Indonesia are other examples where the externally propagated accounting reforms fitted very well into the top political contexts in terms of maintaining legitimacy, but contradicted the public sector accounting traditions, thereby keeping the existing system intact (Khodachek and Timoshenko, 2017;Harun et al, 2012). That public sector accounting reforms have represented facades, simply adding a layer over the existing practices, is also evident in other emerging economies, including Ghana and Benin (Lassou, 2017), Bangladesh (Rajib et al, 2019), Indonesia (Harun et al, 2012), and Nepal and Sri Lanka (Adhikari et al, 2013;Yapa and Ukwatte, 2015). In sub-Saharan Africa the adoption of accrual accounting has engendered more harm in practice by opening up a space for corruption, patronage and neopatrimonialism to proliferate (Bakre et al, 2017;Goddard et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings have reported that presence of conducive policies leads to effective implementation of any accounting reforms [54,67]. In addition, Rajib [9] and Kalulu [52] highlighted that presence of political will and support from the oversight bodies facilitates implementation of accrual-based IPSAS.…”
Section: Factors Influencing Implementation Of Accrual-based Ipsas Inmentioning
confidence: 99%
“…Past studies have reported that developing countries are implementing them as a mere fashion, accompanied by non-preparedness of accountants and auditors [5,6,7,8]. In addition to that, most of them are adopting and implementing accrual-based IPSAS as a response to pressure from development partners [1,9,10,11,12,13]. This indicates that there are factors that influence the implementation of accrual-based IPSAS, in the Public Authorities, Local Government Authorities (LGAs) and Central Government [14,3].…”
Section: Introductionmentioning
confidence: 99%